2016
DOI: 10.1371/journal.pbio.1002443
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Modulatory Proteins and Olfactory Receptor Signaling in the Refinement and Maintenance of Fruitless Expression in Olfactory Receptor Neurons

Abstract: During development, sensory neurons must choose identities that allow them to detect specific signals and connect with appropriate target neurons. Ultimately, these sensory neurons will successfully integrate into appropriate neural circuits to generate defined motor outputs, or behavior. This integration requires a developmental coordination between the identity of the neuron and the identity of the circuit. The mechanisms that underlie this coordination are currently unknown. Here, we describe two modes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 69 publications
(98 reference statements)
5
64
0
Order By: Relevance
“…Because it has been previously shown that the onset of olfactory receptor expression begins around 40 hrs APF28, we were curious to see which, if any, ORs are expressed at this stage. We were able to detect OR transcripts at this stage, but they were expressed at much lower levels as compared to the adult stage (~2 orders of magnitude lower, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it has been previously shown that the onset of olfactory receptor expression begins around 40 hrs APF28, we were curious to see which, if any, ORs are expressed at this stage. We were able to detect OR transcripts at this stage, but they were expressed at much lower levels as compared to the adult stage (~2 orders of magnitude lower, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Upon selection of a “default” olfactory receptor within each sensillum, Notch signaling can relay this information to neighboring ORNs to suppress expression of the “default” receptor and select another olfactory receptor transcriptionally available in the lineage. These modifications might require chromatin regulation, as mutations in alhambra (alh), a chromatin modulator, result in acquisition of the default olfactory receptor expression at the expense of alternate olfactory receptors without modifying the target site of ORN axons in the antennal lobe28. There might be different spatial and temporal requirements of transcription factor and chromatin complexes for each sensilla lineage, as effects of alh mutants are restricted to only few sensilla28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…caused by disruptions to ORN specification programs within at4 sensillum (44). To test whether ORN specification is altered in DIP-η knock down, we labeled Or47b and Or88a ORN cell bodies with RFP and GFP, respectively ( Fig S7D, E).…”
Section: Previous Reports Of Or47b Axon Invasion Of the Va1d Glomerulmentioning
confidence: 99%
“…During development, a putative chromatin modulator Alhambra co-regulates the expression of fruitless and the olfactory receptors involved in sex specific behaviors [77]. Furthermore, fruitless expression is maintained in the adult through the activity of olfactory receptors, CamK signaling, and chromatin modulatory protein p300/CREB-binding protein to maintain sex specific ORN identity [77]. …”
Section: Olfactory System In Drosophila Melanogastermentioning
confidence: 99%